Immunohistochemical expression pattern of metastasis suppressor KISS-1 protein in adenomyosis lesions and normal endometrium. (March 2017) - Kolioulis, I.; Zafrakas, M.; Grimbizis, G.; Miliaras, D.; Timologou, A.; Bontis, J.N.; Tarlatzis, B.C.
Abstract: Objective: Kisspeptins are multifunctional peptides; it has been shown that they act as inhibitors of tumor metastasis in a range of cancers and that they are also involved in cell invasion through regulation of matrix metalloproteinases (MMPs). The aim of this study was to investigate the expression of KISS-1 protein in adenomyosis lesions compared with matched eutopic endometrium, as well as with endometrium from patients without adenomyosis. Study Design: In this comparative, non-interventional study, adenomyosis and corresponding eutopic endometrium samples from women with histologically proven adenomyosis after hysterectomy, and eutopic endometrium samples from women without adenomyosis were analysed. Expression of KISS-1 protein was analyzed immunohistochemically in formalin-fixed, paraffin-embedded adenomyotic tissue specimens (n = 29), matched eutopic endometrium from the same patients (n = 29) and normal endometrium from patients without adenomyosis (n = 29). Results: Using a semi-quantitative immunohistochemical score, we found that KISS-1 protein expression was higher in the adenomyotic as compared with matched eutopic glandular endometrium (p < 0.05), in which in turn KISS-1 protein expression was higher than those from patients without adenomyosis (p < 0.001). The inverse correlation was found in the stroma, between adenomyosis lesions and matched eutopic endometrium (p < 0.01), while no statistically significant correlation was found in KISS-1 protein expression in the stroma between patients with and without adenomyosis. Conclusions: KISS-1 protein expression appears to be up-regulated in adenomyotic as compared with eutopic glandular endometrium of patients with, as well as women without adenomyosis. These findings are suggestive of the involvement of KISS-1 protein in the pathogenesis and maintenance of adenomyosis. Future studies should investigate whether KISS1 protein could be used as a marker for early and minimally invasive detection of adenomyosis, based on its differential protein expression pattern in the eutopic endometrium of patients with and without adenomyosis.